Vlog Task Accompanied with Individualized Pronunciation and Grammar Feedbacks Improve Speaking Ability - Khairuddin Khairuddin (Universitas Pahlawan Tuanku Tambusai, 2022)
Speaking plays both roles as process and objective of learning in language classroom aimed at preparing future communication competence of students. Using Vlog as speaking activities to demonstrate ideas and knowledge can be recreational for the millennial generation. However, grammatical forms and pronunciation accuracy are often neglected areas in such tasks, hence students’ grammatical competence and pronunciation accuracy are not as well developed as their fluency in speaking. The current study innovated to combine Vlog-speaking activities with individualized pronunciation and grammar feedbacks from the teacher in order to not just elevate the millennial students’ Vlog talk performance, but also increase wellness of grammatical forms, accuracy of pronunciation, and clarity of content, hence boost higher confidence. The study measured the effectiveness of this holistic instruction in improving students’ English public speaking skill, and investigated how the students perceived the Vlog task, the individualized grammar feedback, and pronunciation feedback from the teacher. Sixty-two students of health from two equal intact classes at Politeknik Kesehatan Malang were involved as experimental and control groups in the quasi-experiment study. The result of statistical analysis showed that the speech performance of the experimental students was significantly higher than the conventional lecture-treatment control group. In addition, the experimental students’ products of speech seemed to be very creative, fun, and attractive. The results also showed that students had very positive perspectives towards Vlog task although challenging because they felt it could develop their English communication skills